Using the PRECEDE model for causal analysis of mothers preventive behaviors in Iron deficiency anemia of children aged 1-5 years old - Z Jalili; S Faghihzadeh; A.R Heidarnia; M.M Hazavei; S.M Sadat-Hashemi (Journal of Kerman University of Medical Sciences, 2002)
the requirement of iron insreased in growing children due to accelerating of growth.However nutritional iron intake and capacity to adopt iron deficiency are limited.it is not surprising then,that iron deficiency is most common in infants and children.therefore iron deficiency aneamia(IDA) is a topic of importance,not only for the management of individual patients but also for necessary public health measures to improve the diet of the population as a whole.mothers should especially be educated to improve better diet health behaviors for their children.the peresent study was carried out to survey 160 mothers knowledge,attiude and practic towards iron dificiency anemia and their preventive behaviour against this problem in their children by using precede model.analysis of data was done with precede model by path analysis method.results indicated that the following variables had direct  significant effects on mothers preventive behaviors:mothers knowlege,attitude,diet advice from relatives and friends,willingness to participate in relevant classes,availability of ferrus sulfate drop and the financial ability of the family.moreover,mothers preventive behavior had direct significant affect on variable of anemia.finally,the study indicate that PRECEDE model(predisposing enabling and reinforcing factors) could be used to predice preventive behavior of IDA.